Heat triggered molecular restructuring results in triple gel–gel–gel transformations in a Li+-integrated metallogel. Issue 11 (9th September 2022) - Mukherjee, Moupia; Dixit, Manish Kumar; Kumar, Yeeshu; Kalam, Abul; Dubey, Mrigendra
Abstract : Herein, we synthesized a metallogel (1% w/v) which displayed a triple phase as well as morphological transformation under different temperature scales. Abstract : Nature upholds many self-regulatory assemblies which adapt themselves according to the external adverse change and modulate their molecular and/or supramolecular structures to transform into another structural form through dynamic evolution. In a similar fashion, herein, we synthesized a Li + -induced chiral metallogel ensemble (S-TLG ) which undergoes the process of self-adjusting strategy in response to thermal stimuli. The Li + -metallogel was obtained from an l -tartaric acid-based gelator (H 4 TL ) and LiOH in DMSO. When S-TLG was heated up to ∼65 °C, it transformed into a stiffer translucent yellow metallogel (Y-TLG ). Further, heating of Y-TLG in the temperature range of 75–95 °C followed by cooling to ambient room temperature (RT) transformed the yellow gel into an intense red-coloured metallogel (R-TLG ). This thermo-responsive behaviour of the metallogel was also accompanied by a two-step dynamic transformation of fibre–rod–fibre morphology along with supportive changes in molecular structure. To the best of our knowledge, it is the first report of triple morphological transformations in metallogels under the influence of a single stimulus. The mechanism of triple macroscopic gel phase transformation, visible colour change, and morphological evolution along with gelation has been well established using UV-vis, FTIR, PXRD, FE-SEM, fluorescence, 1 H NMR, ESI-mass, rheology and EIS techniques.